DC current sensing capability of microfibre Mach-Zehnder interferometer - Sulaiman, Azlan; Harun, Sulaiman Wadi; Aryanfar, Iman; Ahmad, Harith (Institution of Engineering and Technology, 2012)
Demonstrated is a microfibre Mach-Zehnder interferometer (MZI) structure which is capable of sensing current changes from 0A up to 2.5A with constant fixed wavelength shift, in linear increment pattern. The fine thin copper wire of 0.16mm radii, 60mm length used to carry electrical current is touched to the arms of the MZI. The refractive index of microfibre will change when the temperature of the microfibre rises owing to the flow of electric current. Based on this effect, the resonant wavelength of the MZI will shift. The experimental results show that the wavelength shift is linearly proportional to the square of current and maximum tuning slope 0.32nm/A 2 is achieved using fresh fabricated MZ microfibre. By increasing the touch point area between the copper wire to the MZI structure, the phase shift increased with tuning slope 0.54nm/A 2.